A rare case of cornual molar ectopic pregnancy - Sunil Mulay, Ameya; Gupte, Sanjay; Venkataraman, Gayatri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Gestational trophoblastic disease (GTD) comprises a heterogeneous group of placental disorders characterized by abnormal trophoblastic proliferation. The reported incidence of GTD ranges from 0.2 to 5.8 per 1,000 pregnancies, while ectopic pregnancies account for approximately 0.64% of all pregnancies. The coexistence of ectopic pregnancy with molar pathology is exceptionally uncommon. Hydatidiform mole occurs in about 1 in 2,000 pregnancies, with most cases arising within the uterine cavity.